Battery designs the testing physical of skills for selecting talented taekwondo - Mohammed Mustafa Bakr (Turkish Journal of Kinesiology, 2016)
The aim of this study is to design a battery test physical of skill for the selection of talented young taekwondo Egyptian national project for may have a practical importance of overseeing the selection of young people as well as in the planning of the training process to reach high levels. Applied study on a sample of (750) Individual clubs and youth centers in 14 countries in the Arab Republic of Egypt, and the average age of (11.11 ± 1.06 years), height (143.50 ± 11,09 cm) and weight (42.53 ±10,74kg). Tests were conducted in the period from 17/11/2012 to 29/12/2012. Physical tests following (Ability, Hinge flexibility basin, Agility, Kinetics speed in a level trunk, Kinetics speed in the level face, Endure Performance). Scientific transactions testing laboratories account sincerity and consistency of the tests used in the study. Where the value of the coefficient of sincerity d statistically at the level of the significance of 0.05 is a sign the two sides between the high level and the low level as the value of the coefficient of sincerity between (0.682, 0.932), which indicates that the tests measure what it was made. It was also correlation coefficient d statistically at the level of an indication (0.01) and (0.05) is a sign of the two parties, where the value of P < 0.05 in all tests as they ranged between (0.964-0.998), pointing to a flat these tests. The researcher used the descriptive survey method. Calculated using the weight of the medical balance and use a tape measure to the nearest (0.5) cm. The statistical analysis SPSS was used to apply formulas statistical by calculating: average, standard deviation, correlation, Factor analysis, Six Sigma Score, percentile scores. The results of the standard levels the battery test of physical skills extracted the selection of talented taekwondo sports in the factors of grace the second factor is the dynamic speed. The study concluded that this study concluded to a battery physical of skill tests for selection of talented young taekwondo sport includes tests are (Agility, Hinge flexibility basin, Ability (Broad jump), Kinetics speed in the level trunk, and Kinetics speed in the level face). In addition, the officials of the Egyptian taekwondo federation, trainers and the introduction of the results of this research and application of the battery on the talented young athletes in taekwondo. It will have the greatest impact on the selection of the best elements until access to higher levels of except in the development of appropriate training programs.